2014
DOI: 10.1371/journal.pone.0090662
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Habitat Index of Many Northwest Atlantic Temperate Species Stays Neutral under Warming Projected for 2030 but Changes Radically by 2060

Abstract: Global scale forecasts of range shifts in response to global warming have provided vital insight into predicted species redistribution. We build on that insight by examining whether local warming will affect habitat on spatiotemporal scales relevant to regional agencies. We used generalized additive models to quantify the realized habitat of 46 temperate/boreal marine species using 41+ years of survey data from 35°N–48°N in the Northwest Atlantic. We then estimated change in a “realized thermal habitat index” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 43 publications
2
58
1
Order By: Relevance
“…Under RCP 8.5 emissions scenario, average bottom temperature in Northeast U.S. Continental Shelf system is expected to increase more than 1 °C by 2050 (IPCC, 2014;NOAA, 2015). While the projected increase in bottom temperature in the Gulf of Maine is not expected to exceed the species' maximum temperature tolerance and may even considered favorable, management uncertainties at the southern range limits of the species can be addressed through scenario-based analysis (Hare et al, 2013;Shackell et al, 2014, ASFMC, 2015b. Bioclimate envelope models are valuable tools to; (1) evaluate climate impacts and aid implementation of ecosystem-based fishery management, and (2) generate hypotheses of large scale potential ecological changes in climate-driven marine environment (Cheung et al, 2009).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Under RCP 8.5 emissions scenario, average bottom temperature in Northeast U.S. Continental Shelf system is expected to increase more than 1 °C by 2050 (IPCC, 2014;NOAA, 2015). While the projected increase in bottom temperature in the Gulf of Maine is not expected to exceed the species' maximum temperature tolerance and may even considered favorable, management uncertainties at the southern range limits of the species can be addressed through scenario-based analysis (Hare et al, 2013;Shackell et al, 2014, ASFMC, 2015b. Bioclimate envelope models are valuable tools to; (1) evaluate climate impacts and aid implementation of ecosystem-based fishery management, and (2) generate hypotheses of large scale potential ecological changes in climate-driven marine environment (Cheung et al, 2009).…”
Section: Management Implicationsmentioning
confidence: 99%
“…The spring and fall bottom water temperature increased across the study area over the course of the time D r a f t series (Fig.1: Tanaka and Chen 2016). While the bottom temperature in this area is expected to increase over the foreseeable future, the magnitude of the temperature anomalies through 2060 (~1.5-3 °C) was observed during the 2012 heat wave within the study area (Herbert et al 2012;Shackell et al 2014). The biogeographical response of lobsters to the 2012 Gulf of Maine heat wave demonstrates how changes in water temperature can lead to significant changes in lobster abundance in the inshore Gulf of Maine (Mills et al 2013).…”
Section: Changes In Lobster Distribution and Abundancementioning
confidence: 94%
“…While lobsters may initially respond to climatic variation by tracking optimum temperature and changing distribution, changes in population dynamics, fishing pressure, physiological adaptation, and predator-prey interactions may have a more significant impact in the long-term (Cheung et al 2008;Hale et al 2011;Simpson et al 2011;Shackell et al 2014). This study should be viewed as a first order approximation of changes in lobster D r a f t abundance and subject to future refinement.…”
Section: Utility Of Climate-niche Models Within Management Contextmentioning
confidence: 99%
“…Marine species will need to adapt or migrate in response to their changing habitats, with uncertain and potentially undesired ecological and economic consequences. Global model projections predict lower estimated catch potentials and smaller maximum body weight in marine fish by 2050 (Cheung et al, 2011(Cheung et al, , 2013a, while shifts in the distributions of marine species are projected (Shackell et al, 2014) or already being observed (Pinsky et al, 2013). As environmental changes affect the suitability of marine habitats (i.e.…”
Section: Introductionmentioning
confidence: 99%